Influence of alcohol blend fuels on performance and noise emission in spark ignition engine - Ali Murtaza Ansari; Liaquat Ali Memon; Faheem Ahmed Solangi; Mamdouh T. Ghannam; Mohamed Y.E. Selim (International Journal of Thermofluids)
The depletion of fossil fuel supplies and mounting environmental concerns about global warming are forcing researchers to investigate green fuels like alcoholic fuels, which not only show a discernible decrease in emissions but also increase engine efficiency. Using an engine speed of 1400 rpm and a range of loads, this study examines the effects of different gasoline alcoholic fuel blends on engine performance and noise emissions. The fuel energy content was increased by correctly mixing the ethanol and gasoline in an ultrasonic bath and blending them in different amounts (10 % ethanol + 90 % gasoline; G90E10, 20 % ethanol + 80 % gasoline; G80E20, and pure gasoline; G100). Using a single-cylinder, four-stroke engine with spark ignition, the effects of a gasoline/ethanol mix on power, efficiency, and exhaust emissions were evaluated. An MCR92 Rotational Rheometer was used to analyze the fuel's flow characteristics. However, the brake-specific fuel consumption decreased by 1.24 to 3.1 %, and the brake thermal efficiency for G100, G90E10, and G80E20 fuels achieved at power of 1.91 kW were 22 %, 24 % and 25 %, respectively. The findings demonstrated increases in ethanol content, power, thermal efficiency, and brake specific fuel consumption as the concentration increased. Additionally, adding ethanol reduces toxic exhaust particles. Pure gasoline had a lower heating value, but ethanol was shown to improve all other engine fuel qualities. Pure gasoline fuel (GF) had higher noise emissions than all mixed fuels, a key factor that changes based on the kind of fuel. The air-fuel equivalency ratio also rises to an amazing number because to the leaning effect of the ethanol, which makes the combustion nearly stoichiometric.